2007
DOI: 10.1590/s0004-27492007000100030
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis retinochoroiditis after photodynamic therapy and intravitreal triamcinolone for a supposed choroidal neovascularization: a case report

Abstract: The purpose is to report a complication after photodynamic therapy (PDT) and intravitreal triamcinolone for a presumed choroidal neovascularization in age-related macular degeneration. Photodynamic therapy and intravitreal triamcinolone were used in an 84-year-old man with choroidal neovascularization in the left eye. Forty-five days after therapy, the patient returned with a severe necrotizing uveitis in the posterior pole and vitritis. Laboratory investigation disclosed a high anti-Toxoplasma IgG titer. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The authors observed stable/improved visual acuity and stabilized CNV diameters after PDT at 4 years’ follow-up [ 124 ]. In other case reports, PDT has been combined with either bevacizumab or with intravitreal triamcinolone acetonide in the treatment of CNV associated with toxoplasmosis [ 125 , 126 ].…”
Section: Reviewmentioning
confidence: 99%
“…The authors observed stable/improved visual acuity and stabilized CNV diameters after PDT at 4 years’ follow-up [ 124 ]. In other case reports, PDT has been combined with either bevacizumab or with intravitreal triamcinolone acetonide in the treatment of CNV associated with toxoplasmosis [ 125 , 126 ].…”
Section: Reviewmentioning
confidence: 99%
“…[8] This may be explained by the absence of appropriate anti-toxoplasmic coverage. However, Backhouse et al ., described a case of fulminant toxoplasmic retinochoroiditis following IVTA despite simultaneous anti-toxoplasmic coverage, which led to a vitrectomy with silicone oil placement for cosmetic globe preservation similar to our second case.…”
Section: Discussionmentioning
confidence: 99%
“…[1516] Pars plana vitrectomy is performed to treat persistent vitreous opacities or vitreoretinal traction. A newer fluoroquinolone, trovafloxacin, has potent anti-Toxoplasma activity and appears promising.…”
Section: Infective Posterior Uveitismentioning
confidence: 99%